Assessing Proactive Investigation Techniques Against Corruption: A Comparative Study of Indonesia, the United States, Hong Kong, and Singapore - Khristiya Lutfiasandhi; Ayu Dian Ningtias; Dewi Ajeng Sintia Putri (Universitas Islam Lamongan, 2026)
The Indonesian Criminal Procedure Code (KUHAP) does not formally recognize the term Operasi Tangkap Tangan (OTT) or